2021
DOI: 10.1002/fsn3.2612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pangasius (Pangasius hypophthalmus) and Skipjack Tuna (Sarda orientalis) mince blend on the quality of fish products: Ways to utilize resources and nutrition in Bangladesh

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…The proximate composition of raw fillet and boiled mince of fish and chicken were analyzed (Figure 1). Hoque et al (2021) found moisture of raw pangas fish 69.75±0.96%, protein 19.49±0.71%, lipid 8.84±0.20%, ash 1.71±0.38% strongly matched with the data found in this experiment. Another study conducted by Rathod and Pagarkar, (2013) revealed the moisture, protein, lipid, ash of raw pangas meat to be 76.62%, 14.37%, 6.76% and 2.25% respectively, which also more or less matched with the obtained data of raw pangas fillet.…”
Section: Raw Fillet and Boiled Mincesupporting
confidence: 89%
“…The proximate composition of raw fillet and boiled mince of fish and chicken were analyzed (Figure 1). Hoque et al (2021) found moisture of raw pangas fish 69.75±0.96%, protein 19.49±0.71%, lipid 8.84±0.20%, ash 1.71±0.38% strongly matched with the data found in this experiment. Another study conducted by Rathod and Pagarkar, (2013) revealed the moisture, protein, lipid, ash of raw pangas meat to be 76.62%, 14.37%, 6.76% and 2.25% respectively, which also more or less matched with the obtained data of raw pangas fillet.…”
Section: Raw Fillet and Boiled Mincesupporting
confidence: 89%
“…This might be because rural residents had higher energy expenditure in their daily work, especially in agricultural and domestic activities like fuelwood and water collection (Saaka et al, 2017 ). Also, it might be due to lower incomes in rural areas restricting food consumption, but having access to fresh fruits at different seasons (Hoque et al, 2021 ; Perrin et al, 2018 ). It might also be as a result of less access to and use of public transport which makes them walk and this helps them in burning down some excess fats than the sedentary lifestyles in the urban areas since the World Health Organization recommends exercises in the form of walking for healthy living (Owade et al, 2020 ; Yankah et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was emphasized that the type of fish, as the main ingredient, influences the cooking method for making fish balls. A previous study produced fish balls from a mixture of P. hypophthalmus and Sarda orientalis meat using two methods: incubation at 50 °C for 60 minutes followed by heating at 100°C for 30 minutes, and pressure steaming at 120 °C and 15 lbs/inch 2 for 20 minutes (Hoque et al, 2021). Another report applied heat treatment to make fish balls from Hypophthalmichthys molitrix by soaking the meat in warm water (40 °C) for 30 minutes, then increasing the temperature gradually to 90 °C for 20 minutes (Fan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%